Participatory farmer video production - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Short learning videos that capture new or improved agricultural technologies and practices are created by farmers, for farmers. These videos, available on the Digital Green Web site, are shared among similar communities through facilitated discussion.